CO-INOCULATION OF SOYBEAN (GLYCINE MAX) WITH ACTINOMYCETES AND BRADYRHIZOBIUM JAPONICUM ENHANCES PLANT GROWTH, NITROGENASE ACTIVITY AND PLANT NUTRITION - Pongrawee Nimnoi (2018)
The aim of this study was to determine the potential of the endophytic actinomycetes that produce plant growth promoters used as co-inoculants with Bradyrhizobium japonicum to promote the growth of soybean. These endophytes exhibited the potential to enhance plant growth, nitrogenase activity of root nodules and plant nutrient uptake. Co-inoculum of B. japonicum with Nocardia alba conferred the maximum yield of root and shoot dry weight. All single-inoculated actinomycetes strains had the ability to enhance plant growth. Noc. alba and Nonomuraea rubra increased total plant dry weight up to 2.14-fold and 2.11-fold, respectively, when compared to the uninoculated controls. Co-inoculations of B. japonicum with each of Noc. alba, Non. Rubra, and Actinomadura glauciflava increased acetylene reduction activity up to 1.7 to 2.7-fold. For plant mineral composition, all of co-inoculation treatments significantly increased the nutrient levels of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe) and zinc (Zn) within a soybean plant. © 2014 Copyright Taylor and Francis Group, LLC.